A multi-objective electromechanical impedance technique to identify debonding in RC beams flexural strengthened with FRP. (2017) - Perera, Ricardo; Sun, Rui; Sevillano, Enrique; Ruiz, Antonio
Abstract: Identification of the intermediate crack debonding in FRP strengthened reinforced concrete structures at its earliest stages, is a very challenging task due to its complexity and local nature. Impedances measured at high frequencies are sensitive enough to detect local damage. In this work, a multi-objective model updating approach is developed able to identify debonding damage in reinforced concrete beams flexural strengthened with FRP. An objective function is formulated from the impedance measurements captured for each PZT sensor resulting in a multi-objective model updating procedure. The numerical simulation of the structure is carried out by using a spectral approach, in contrast to the conventional finite element method, due to its ability to provide accurate solutions at high frequencies. The proposed approach is evaluated on a real-scale FRP-strengthened RC beam instrumented with several PZT sensors and tested with different levels of damage.